Assessing the impact of liberalisation policies on the Greek labour market: an insider–experts' view from the perspective of the varieties of liberalisation. Issue 6 (5th October 2020) - Tourtouri, Myrto; Pavlopoulos, Dimitris; Papatheodorou, Christos
Abstract: During the recent Great Recession (2008–2018), Greece has become the prototype example of the implementation of austerity policies in Europe. Contrary to public discourse, these austerity policies were complemented by substantial labour market reforms that promoted employment and wage flexibility. This article aims to present a theory‐driven understanding of the implementation and the effects of these reforms. For this purpose, we employ a qualitative study consisting of semi‐structured interviews with 50 labour market experts—government officials and labour lawyers, academics, labour union representatives and employer association representatives. Using Thelen's framework on the Varieties of Liberalization, we conclude that, contrary to the initial aims of the reforms, Greece followed a trajectory of direct deregulation, reducing considerably the level of both coordination between employers and workers, and coverage of employment protection. The interviews show that the dismantling of collective bargaining system was the most decisive move in this path.